Hypersensitivities following allergen antigen recognition by unconventional T cells. Issue 10 (13th April 2020) - de Lima Moreira, Marcela; Souter, Michael N. T.; Chen, Zhenjun; Loh, Liyen; McCluskey, James; Pellicci, Daniel G.; Eckle, Sidonia B. G.
Abstract: Conventional T cells recognise protein‐derived antigens in the context of major histocompatibility complex (MHC) class Ia and class II molecules and provide anti‐microbial and anti‐tumour immunity. Conventional T cells have also been implicated in type IV (also termed delayed‐type or T cell–mediated) hypersensitivity reactions in response to protein‐derived allergen antigens. In addition to conventional T cells, subsets of unconventional T cells exist, which recognise non‐protein antigens in the context of monomorphic MHC class I‐like molecules. These include T cells that are restricted to the cluster of differentiation 1 (CD1) family members, known as CD1‐restricted T cells, and mucosal‐associated invariant T cells (MAIT cells) that are restricted to the MHC‐related protein 1 (MR1). Compared with conventional T cells, much less is known about the immune functions of unconventional T cells and their role in hypersensitivities. Here, we review allergen antigen presentation by MHC‐I‐like molecules, their recognition by unconventional T cells, and the potential role of unconventional T cells in hypersensitivities. We also speculate on possible scenarios of allergen antigen presentation by MHC‐I‐like molecules to unconventional T cells, the hallmarks of such responses, and the expected frequencies of hypersensitivities within the human population.